(untitled) (Revista revoluciones, 2022)
This article carries out a historical review of documents that, seen from a genealogical deconstructivist perspective, reveals the way in which racism has configured the institution and concept education to serve as an instrument of domination, enslavement and segregation in the West, Latin America and Colombia. This, reflecting on the Western emergence of the concept, its use during the Spanish colonization in America, and its development until today. The Education device, defined as a Western institution of physical and cognitive domination (Walsh, 2013) based on racism (Soler, 2017), that includes within its actions non-schooled formative processes (Molina, 2020) must be redesigned by ethno-education and postcolonial communities to guard against the traps of contemporary racism, incidentally, to lay the foundations of an Afro-descendant and indigenous epistemology that prints a new concept of education based on justice and equity.